Rational pharmacotherapy of chronic obstructive pulmonary disease in elderly patients with cardiac arrhythmias: the role of a betaadrenoblocker bisoprolol - D. A. Kadaeva; K. A. Masuev; S. M. Datsieva; M. I. Ibragimova (Кардиоваскулярная терапия и профилактика)
Aim. To study bisoprolol effectiveness and safety in elderly patients with chronic obstructive pulmonary disease (COPD) and cardiac arrhythmias; to evaluate bisoprolol effects on bronchial resistance. Material and methods. All patients (n=65) were divided into 2 groups: Group I, receiving bisoprolol (n=34), and Group II (n=31), a control group not receiving beta-adrenoblockers (BAB). All participants underwent general clinical examination, 24-hour Holter ECG monitoring and lung function assessment by spirography. The titration of bisoprolol dose started from 2,5 mg/d. In case of no bradycardia, hypotension, or increased bronchial resistance, the dose was titrated up to 5 mg/d. The repeat examination was performed 12 weeks later. Results. BAB therapy was associated with a reduction in ventricular and supraventricular extrasystolia, including supraventricular tachycardia “runs” and atrial fibrillation paroxysms, among the majority of COPD patients. In the control group, on the contrary, the incidence of cardiac arrhythmias increased, compared to the baseline (p<0,05). In Group I, the following lung function parameters significantly increased by the end of the study: FVC (p<0,05), FEV1 (p<0,01), and FEF25% (p<0,05). In Group II, lung function parameters significantly increased, including FVC (p<0,05), FEV1 (p<0,01), FEF25% (p<0,01), and FEF50% (p<0,01). Conclusion. Bisoprolol did not increase bronchial resistance. Adding this highly selective BAB to a complex therapy of elderly patients with COPD resulted in cardiac arrhythmia correction, heart rate reduction, and quality of life improvement.